Social Utility of Mobile Phone Technology by Undergraduate University Students in Nairobi, Kenya - Wasiaya, O. C.; Serede, S. K.; Mberia, K. H. (Archives of Business Research, 2021)
This study investigated social utility as a gratification factor influencing mobile phone technology use by public university undergraduate students in Nairobi, Kenya. The objective of the study was to examine the influence of social utility on undergraduate university students’ use of mobile phone technology. The study employed media technological determinism theory. Target population was 246,871 undergraduate university students in public universities in Nairobi, Kenya. The study employed quantitative design. Self-administered questionnaires were used as data collection tools. The study utilized purposive sampling to arrive at a sample size of 573 undergraduate students. The data was analyzed using descriptive statistics and then processed using the Statistical Package for Social Sciences (SPSS) version 23. Findings revealed that mobile phone technology has become essential in social utility activities among undergraduate university students. The research concluded that the more the need for social utility, the more the need for mobile phone technology use among undergraduate university students. The research recommended that software developers should develop a specific mobile phone software for university students to use for social utility and that another research could be carried among postgraduate students and among private universities to find out other gratification factors that may be influencing mobile phone technology use.